Analysis of Performance Instabilities of Hafnia‐Based Ferroelectrics Using Modulus Spectroscopy and Thermally Stimulated Depolarization Currents. (1st February 2018) - Fengler, Franz P. G.; Nigon, Robin; Muralt, Paul; Grimley, Everett D.; Sang, Xiahan; Sessi, Violetta; Hentschel, Rico; LeBeau, James M.; Mikolajick, Thomas; Schroeder, Uwe
Abstract: The discovery of the ferroelectric orthorhombic phase in doped hafnia films has sparked immense research efforts. Presently, a major obstacle for hafnia's use in high‐endurance memory applications like nonvolatile random‐access memories is its unstable ferroelectric response during field cycling. Different mechanisms are proposed to explain this instability including field‐induced phase change, electron trapping, and oxygen vacancy diffusion. However, none of these is able to fully explain the complete behavior and interdependencies of these phenomena. Up to now, no complete root cause for fatigue, wake‐up, and imprint effects is presented. In this study, the first evidence for the presence of singly and doubly positively charged oxygen vacancies in hafnia–zirconia films using thermally stimulated currents and impedance spectroscopy is presented. Moreover, it is shown that interaction of these defects with electrons at the interfaces to the electrodes may cause the observed instability of the ferroelectric performance. Abstract : Evidence for the presence of singly and doubly positively charged oxygen vacancies in hafnia–zirconia films, using thermally stimulated currents and impedance spectroscopy, is presented. Moreover, it is shown that the interaction of these defects with electrons at the interfaces to the electrodes may cause the often observed instability of the ferroelectric response during field cycling.